Ion-dependent gating of kainate receptors - Bowie, Derek (The Journal of physiology, 2010)
Ligand-gated ion channels are an important class of signalling protein that depend on small chemical neurotransmitters such as acetylcholine, l -glutamate, glycine and Î³-aminobutyrate for activation. Although numerous in number, neurotransmitter substances have always been thought to drive the receptor complex into the open state in much the same way and not rely substantially on other factors. However, recent work on kainate-type (KAR) ionotropic glutamate receptors (iGluRs) has identified an exception to this rule. Here, the activation process fails to occur unless external monovalent anions and cations are present. This absolute requirement of ions singles out KARs from all other ligand-gated ion channels, including closely related AMPA- and NMDA-type iGluR family members. The uniqueness of ion-dependent gating has earmarked this feature of KARs as a putative target for the development of selective ligands; a prospect all the more compelling with the recent elucidation of distinct anion and cation binding pockets. Despite these advances, much remains to be resolved. For example, it is still not clear how ion effects on KARs impacts glutamatergic transmission. I conclude by speculating that further analysis of ion-dependent gating may provide clues into how functionally diverse iGluRs families emerged by evolution. Consequently, ion-dependent gating of KARs looks set to continue to be a subject of topical inquiry well into the future.